High-strength ceramsite prepared from sintered iron ore waste powder and fly ash and preparation method of high-strength ceramsite

By using iron ore waste powder and flour ash as the main raw materials, and adding calcium fluoride and pussy soil, high -strength pottery grains are prepared, solving the problem of high water absorption rate and relying on clay. Ceramics preparation.

CN119330741AInactive Publication Date: 2025-01-21TAIYUAN UNIVERSITY OF TECHNOLOGY +1

Patent Information

Application Number
CN202411497913.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art requires a large amount of clay consumption when preparing ceramite using iron ore waste powder and fly ash, and the water absorption rate of the ceramite is high, which affects its performance in humid environments.

Method used

It uses iron ore waste powder and fly ash as the main raw materials, adds calcium fluoride as a flux to lower the melting point, and achieves surface vitrification through the molten state of the material to enhance the material strength. At the same time, bentonite is added to enhance firing performance and improve workability.

Benefits of technology

The prepared high -intensity pottery has a low water absorption rate, which can maintain performance in a humid environment. It is low and easy to obtain. It can effectively use solid waste to reduce pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330741A_ABST
    Figure CN119330741A_ABST
Patent Text Reader

Abstract

The invention relates to the field of building materials, in particular to high-strength ceramsite prepared from sintered iron ore waste powder and fly ash and a preparation method of the high-strength ceramsite. Comprising the following raw materials in parts by mass: 45.07-154.84 parts of iron ore waste powder, 0-101.41 parts of fly ash and 0-65.45 parts of bentonite, and 0-21.82 parts of calcium fluoride is added as an additive after the iron ore waste powder, the fly ash and the bentonite are uniformly mixed. The high-strength ceramsite is reasonable in design, the iron ore waste powder, the fly ash and the bentonite serve as main raw materials, the characteristics that silicon dioxide, aluminum oxide and other substances are melted and recombined under the high-temperature condition and have high strength are utilized, the water absorption rate of the high-strength ceramsite is about 0%, and the heat insulation or cold insulation performance of the high-strength ceramsite cannot be affected in the humid environment; and the low water absorption does not influence the setting of the water cement ratio of the concrete. The iron ore waste powder and fly ash high-strength ceramsite can be used as concrete aggregate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to high-strength ceramsite prepared from sintered iron ore waste powder and fly ash and a preparation method thereof. Background Art

[0002] Iron ore waste powder is the solid waste generated by the crushing, grinding, magnetic separation, flotation and gravity separation of iron ore, and is the main source of environmental pollution; fly ash is the main solid waste discharged by coal-fired power plants, and is one of the largest industrial waste residues in my country. With the development of the power industry, the fly ash emissions from coal-fired power plants have increased year by year. In 2015, the national fly ash production reached 570 million tons. As a large amount of solid waste, the disposal of iron ore waste powder and fly ash has received national attention. Firing ceramsite can be used as a resource-based, harmless and reduced method to make iron ore waste powder and fly ash available. Some processes use iron ore waste powder as the main raw material, add clay, binder and other auxiliary materials, and prepare ceramsite through batching, mixing, granulation and sintering, which consumes a large amount of arable land clay. Summary of the invention

[0003] The present invention overcomes the deficiencies of the prior art and provides a high-strength ceramsite prepared from sintered iron ore waste powder and fly ash and a preparation method thereof. The present invention uses iron ore waste powder as the main raw material, and the additive calcium fluoride is used as a flux in the present invention to reduce the melting point, and the surface of the material is vitrified in the molten state, which enhances the strength of the material and greatly reduces the water absorption rate; the addition of bentonite enhances the firing performance and improves the processability. The high-strength ceramsite prepared by the present invention is a high-strength aggregate that can promote the utilization of solid waste and reduce the mining of natural stones. The ingredients and process of the present invention can reduce the water absorption rate of the material and avoid the influence of the humid environment on the material performance, and the application direction is building materials, which can utilize a large amount of solid waste and realize the transformation of waste into treasure.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is: a high-strength ceramsite prepared by sintering iron ore waste powder and fly ash, comprising the following raw materials in mass ratio:

[0005]

[0006] Since the main components of iron ore waste powder are silicon dioxide and aluminum oxide, it is the main raw material for ceramics; the main components of fly ash are silicon dioxide and aluminum oxide (relative to iron ore waste powder, its aluminum oxide content is higher); bentonite has high plasticity and strong adhesion, and is used as a binder; calcium fluoride is used as a flux to reduce the maximum sintering temperature. Combined with the control of the maximum sintering temperature and the duration of the maximum temperature, the comprehensive effect forms a closed shell outside the material, reduces the water absorption rate of the material, and improves the strength of the material.

[0007] Furthermore, the silicon dioxide content of the iron ore waste powder is 51.16%, and the aluminum oxide content is 22.74%; the silicon dioxide content of the fly ash is 51%, and the aluminum oxide content is 35.31%.

[0008] The present invention also provides a method for preparing high-strength ceramsite prepared from the above-mentioned sintered iron ore waste powder and fly ash, comprising the following steps:

[0009] A. Preparation of high-strength ceramsite blanks with iron ore waste powder and fly ash;

[0010] A1. Drying raw materials and admixtures;

[0011] A2. Weigh the raw materials and admixtures in the mass ratio, use a ball mill to mix the iron ore waste powder, fly ash and bentonite, then add calcium fluoride and mix evenly;

[0012] A3. Use a vibrating screen to sift out the powder;

[0013] A4, using the sieved powder in A3 to make a green body;

[0014] A5. Dry the blank;

[0015] B. Sintering the green body to prepare high-strength ceramsite: Place the green body in the furnace and set the heating curve for sintering. The heating rate is 15°C / min, and the temperature is maintained at 350°C for 15 minutes. Continue to heat up to the set maximum sintering temperature of 950-1350°C for 3 to 15 minutes, and then cool down naturally to obtain high-strength ceramsite.

[0016] Furthermore, in step A1, the drying temperature is 105° C., and in step A2, a planetary ball mill is used as the ball mill at 400 rpm for 20 minutes.

[0017] Furthermore, in step A3, a vibrating screen with a diameter of 30 cm and an aperture of 100 mesh is used for 10 minutes to sieve out the powder.

[0018] Compared with the prior art, the present invention has at least the following beneficial effects:

[0019] First, waste iron ore powder, fly ash and bentonite are low-cost and easy to obtain, which can reduce the raw material cost of high-strength expanded clay and reduce the pollution of waste iron ore powder and fly ash to the environment.

[0020] Second, the production cycle of high-strength expanded clay produced by sintering is shorter than that of unfired expanded clay.

[0021] Third, this high-strength expanded clay has a compact internal structure and high strength.

[0022] Fourth, the water absorption rate of this high-strength expanded clay is about 0%, and a humid environment will not affect its thermal insulation or cooling performance, and the low water absorption rate will not affect the setting of the water-cement ratio of concrete.

[0023] Fifth, the present invention is reasonably designed, using iron ore waste powder, fly ash and bentonite as main raw materials, and utilizing silicon dioxide, aluminum oxide and other materials to melt under high temperature conditions and reorganize the materials, so that the ceramsite has the characteristics of high strength and can be used as concrete aggregate.

[0024] Sixth, the existing process uses iron ore waste powder as the main raw material, adds clay, binder and other auxiliary materials, and prepares ceramsite through batching, mixing, granulation and sintering, which consumes a large amount of arable land clay. The present invention mixes iron ore waste powder with fly ash to improve resource utilization, reduce pollutant emissions, find the best ratio, and prepare high-strength ceramsite with better performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The change of ceramsite size after sintering with 10 different ingredients at different high temperatures.

[0026] Figure 2 Table 3 shows the XRD composition analysis of high-strength ceramsite.

[0027] Figure 3 This is a bar chart of the compressive strength of 10 ingredients after different sintering curves.

[0028] Figure 4 The water absorption and apparent density of the 10 ingredients after the second sintering curve acts on them one hour later.

[0029] Figure 5 It is the compressive strength of 10 kinds of ingredients after the second sintering curve.

[0030] Figure 6 These are the compressive strength test results of ceramsite with new ingredients at different maximum sintering temperatures.

[0031] Figure 7 These are the XRD diagrams of high-strength ceramsite with new ingredients at different maximum sintering temperatures.

[0032] Figure 8 Figure 3 shows the microstructure of high-strength expanded clay with new ingredients at different maximum sintering temperatures, where (a) and (b) are microscopic images of the interior of high-strength expanded clay at 10 microns and 100 nanometers after the maximum sintering temperature of 1150°C; (c) and (d) are microscopic images of the interior of high-strength expanded clay at 10 microns and 100 nanometers after the maximum sintering temperature of 1200°C; (e) and (f) are microscopic images of the interior of high-strength expanded clay at 10 microns and 100 nanometers after the maximum sintering temperature of 1250°C. DETAILED DESCRIPTION

[0033] The present invention is further described below in conjunction with specific embodiments.

[0034] The present invention uses iron ore waste powder as the main raw material, adds calcium fluoride as a flux to reduce the melting point, and the material is molten to achieve surface vitrification, enhance the material strength and greatly reduce the water absorption rate; adding bentonite enhances the firing performance and improves the processability. The ingredients and process of the present invention can reduce the water absorption rate of the material and avoid the influence of the humid environment on the material performance. The application direction is building materials, and solid waste can be used in large quantities to achieve waste into treasure. The high-strength ceramsite obtained by the present invention can promote the utilization of solid waste and reduce the mining of natural stones.

[0035] The high-strength ceramsite prepared by sintering waste iron ore powder and fly ash is made of waste iron ore powder, fly ash and bentonite as raw materials, according to the following formula (parts by mass):

[0036]

[0037] The preparation method of the high-strength ceramsite prepared from the above-mentioned sintered iron ore waste powder and fly ash is as follows:

[0038] A. Preparation of high-strength ceramsite blanks with iron ore waste powder and fly ash;

[0039] A1. Drying raw materials and admixtures;

[0040] A2. Use a ball mill to mix the iron ore waste powder, fly ash and bentonite, then add calcium fluoride and mix evenly;

[0041] A3. Use a vibrating screen to sift out the powder;

[0042] A4, using the sieved powder in A3 to make a green body;

[0043] A5. Dry the blank;

[0044] B. Sintering the green body to prepare high-strength ceramsite: Place the green body in the furnace and set the heating curve for sintering. The heating rate is 15°C / min, and the temperature is maintained at 350°C for 15 minutes. Continue to heat up to the set maximum sintering temperature of 950-1350°C for 3 to 15 minutes, and then cool down naturally to obtain high-strength ceramsite.

[0045] The above-mentioned iron ore waste powder, fly ash, bentonite, and calcium fluoride were added to conduct experiments. The specific composition ratios and results of the experimental samples are shown in Tables 3 to 6 below.

[0046] Table 7 shows the apparent density, compressive strength and water absorption of the optimized new batch (set to 160 g of iron ore waste powder without adding fly ash, bentonite or calcium fluoride) under different sintering curves.

[0047] Table 1 Sintering parameters

[0048]

[0049] Table 2 Optimized sintering parameters

[0050]

[0051] Table 3 Iron ore waste powder, fly ash, bentonite, and calcium fluoride are mixed in the following mass proportions, with a maximum sintering temperature of 950°C and a maximum temperature duration of 6 minutes

[0052]

[0053] Table 4 Iron ore waste powder, fly ash, bentonite and calcium fluoride are mixed in the following mass proportions, the highest sintering temperature is 1150℃, and the highest temperature duration is 9min

[0054]

[0055] Table 5 Iron ore waste powder, fly ash, bentonite and calcium fluoride are mixed in the following mass ratios, with a maximum sintering temperature of 1050°C and a maximum temperature duration of 15 minutes

[0056]

[0057]

[0058] Table 6 Iron ore waste powder, fly ash, bentonite and calcium fluoride are mixed in the following mass ratios, with a maximum sintering temperature of 1100°C and a maximum temperature duration of 12 minutes

[0059]

[0060] Table 7 Apparent density, compressive strength and water absorption of the optimized new ingredients under different sintering curves

[0061]

[0062] from Figure 1 The change in the size of the ceramsite after sintering at different high temperatures can be seen. It is obvious that in sintering curves (3) and (4), the ceramsite showed obvious melting at the maximum temperatures of 1350℃ and 1250℃ respectively. Sintering curves (6) and (9) also had similar melting problems due to excessively high temperatures and long sintering times, so these experiments were cancelled. Sintering curve (8) was cancelled because the same parameters as sintering curve (2) were used. The maximum temperature of sintering curve (1) was 950℃, which resulted in low compressive strength values, so the maximum temperature of sintering curve (7) was adjusted to 1100℃. Similarly, the maximum temperature of sintering curve (5) was 1050℃, but the compressive strength produced was not high, so the maximum temperature of sintering curve (10) was increased to 1200℃.

[0063] Figure 2Corresponding to the XRD component analysis of high-strength ceramsite in Table 3, the XRD analysis of the high-strength ceramsite prepared in Example 1 shows the presence of silica and feldspar. The sample has a high content of bentonite, which causes expansion during sintering, thereby reducing the compressive strength. The high-strength ceramsite obtained in Example 5 contains more feldspar than the high-strength ceramsite obtained in Example 3, resulting in reduced strength. The three types of high-strength ceramsite obtained in Example 2, Example 4 and Example 7 mainly contain silica and mullite, and their compressive strength is also low due to the influence of mullite. The feldspar content in the two high-strength ceramsites obtained in Example 5 and Example 9 is high, resulting in lower strength. Corundum and spinel are well-known for their strength-enhancing properties. They appear in the three high-strength ceramsite formulas in Example 6, Example 8 and Example 10, which help to improve the compressive strength of the obtained high-strength ceramsite.

[0064] Figure 4 The water absorption and apparent density of the 10 ingredients after the second sintering curve for 1 hour are shown. The results show that the higher the density, the lower the water absorption. The average strength of ingredient 3 is the highest, with a density of 2.53×10 3 kg / m 3 , the water absorption rate is 0.5%.

[0065] Figure 5 The compressive strength of the 10 ingredients in Table 4 after the second sintering curve (maximum sintering temperature 1150℃, maximum temperature duration 9min). Among them, the strength of mix 3 is the highest, which is 43.36 MPa, followed by mixes 6, 8 and 10. The strength of mix 1 is the lowest. After optimization, the new mix composition is set to 160g of iron ore waste powder without adding fly ash, bentonite or calcium fluoride.

[0066] Figure 7 The XRD diagram of high-strength ceramsite with new ingredients at different maximum sintering temperatures shows that the main material components remain consistent at different sintering temperatures. The main components include silicon dioxide, corundum-Al2O3, and spinel-Al2MgO4.

[0067] Figure 8 The microstructure of high-strength ceramsite with new ingredients at different maximum sintering temperatures. Microstructural analysis shows that at 1150°C, many small pores are still not closed, and gases can gradually escape. At 1200°C, the pores close, forming a denser structure. At 1250°C, the pores expand, reducing the overall strength. At a finer scale (100nm), the crystalline phase transitions from rough at 1150°C to smooth at 1200°C and then to rough at 1250°C, reflecting the change in structure.

[0068] The present invention utilizes the relationship between the amount and apparent density of four raw materials (including iron ore waste powder, fly ash, bentonite, and calcium fluoride) and uses stepwise regression technology to fit and optimize the ingredients. This method successfully optimizes the test ratio and achieves the expected results. The method of producing high-strength aggregate using iron ore waste powder, fly ash and bentonite promotes the utilization of solid waste and reduces the mining of natural stones. According to the results of compressive strength test, XRD analysis and microstructure inspection, the following conclusions are drawn:

[0069] (1) The mass ratio of iron ore waste powder, fly ash, bentonite and calcium fluoride is 154.84:0:0:5.16, the maximum sintering temperature is 1150℃, the sintering time is 9 minutes, and the average compressive strength of the obtained high-strength ceramsite is 43.35MPa. The main components are SiO2 and feldspar.

[0070] (2) Iron ore waste powder can be used as the only raw material for sintering ceramsite. Without adding calcium fluoride, the maximum sintering temperature is 1200℃, the sintering time is 3 minutes, and the average compressive strength of the sintered high-strength ceramsite is 52.33MPa. It is mainly composed of SiO2, corundum-Al2O3, and spinel-Al2MgO4.

[0071] (3) The optimal sintering temperature is 1200℃ and maintained for 3 minutes. The sintered high-strength ceramsite has a water absorption rate of 0% and a relatively compact internal structure, and can be used as concrete aggregate.

[0072] High-strength ceramsite is not only a sustainable alternative, but also a means of reducing environmental pollution. The development of high-strength ceramsite also highlights the prospects of eco-friendly building materials and promotes environmentally responsible research and development practices.

Claims

1. A high-strength ceramsite prepared from sintered iron ore waste powder and fly ash, characterized in that: The invention comprises the following raw materials in parts by weight:

2. The high-strength ceramsite prepared from sintered iron ore waste powder and fly ash according to claim 1, characterized in that: The iron ore waste powder has a silicon dioxide content of 51.16%, an aluminum oxide content of 22.74%, and an iron oxide content of 11.76%; the fly ash has a silicon dioxide content of 51% and an aluminum oxide content of 35.31%.

3. The method for preparing high-strength ceramsite prepared from sintered iron ore waste powder and fly ash according to claim 1, characterized in that: The following steps are involved: A. Preparation of high-strength ceramsite blanks with iron ore waste powder and fly ash; A1. Drying raw materials and admixtures; A2. Weigh the raw materials and admixtures in the mass ratio, use a ball mill to mix the iron ore waste powder, fly ash and bentonite, then add calcium fluoride and mix evenly; A3. Use a vibrating screen to sift out the powder; A4, using the sieved powder in A3 to make a green body; A5. Dry the blank; B. Sintering the green body to prepare high-strength ceramsite: Place the green body in the furnace and set the heating curve for sintering. The heating rate is 15°C / min, and the temperature is maintained at 350°C for 15 minutes. Continue to heat up to the set maximum sintering temperature of 950-1350°C for 3 to 15 minutes, and then cool down naturally to obtain high-strength ceramsite.

4. The method for preparing high-strength ceramsite prepared from sintered iron ore waste powder and fly ash according to claim 3, characterized in that: The drying temperature in step A1 is 105° C., and the ball mill in step A2 uses a planetary ball mill at 400 rpm for 20 minutes.

5. The method for preparing high-strength ceramsite prepared from sintered iron ore waste powder and fly ash according to claim 3, characterized in that: In step A3, a vibrating sieve with a diameter of 30 cm and an aperture of 100 mesh is used for 10 minutes to sieve out the powder.

Citation Information

Patent Citations

  • Solid waste porcelain granule in iron ore mine and ore dressing plant and preparation method thereof

    CN101525219A

  • Iron tailing ceramsite for building material and preparation method thereof

    CN110066126A

  • Core-shell structure ceramsite based on iron tailings and alkaline residues and preparation method of core-shell structure ceramsite

    CN110615667A

  • High-strength ceramsite using slag as aggregate and preparation method thereof

    CN110698214A

  • Sintered perlite waste mineral powder and fly ash ultra-light thermal insulation ceramsite and preparation method thereof

    CN117756548A

Cited By

  • Environment-friendly high-strength ceramsite and preparation method thereof

    CN120943552A